Loading...

x-2(x)+4/x^2 -4=x-2x+4/x^2 -4=-x-4+4/x^2

(-9x^2/√x) + 4= [-9x^2/x^(1/2)] + 4= (-9x^2)[x^(-1/2)] + 4= -9x^[2 + (-1/2)] + 4= -9x^(2 - 1/2) + 4= -9x^(3/2) + 4= -9√x^3 + 4= -9√[(x^2)(x)] + 4= -9x√x + 4Or,(-9x^2/√x) + 4= [(-9x^2)(√x)/(√x)(√x)] + 4= [(-9x^2)(√x)/√x^2] + 4= [-9(x)(x)(√x)/x] + 4 simplify x= -9x√x + 4

x+4=2 x=2-4 (taking 4 to other side ) x=-2 ------------------------------------------------------------------------------------------------------------------ substituting x=-2 x+4=2 -2+4=2 2=2

x^2/x +2=4/x +2 (x^2/x)-(4/x)=0 (x^2-4)/x=0 x^2-4=0 (x+2)(x-2)=0 x=±2

0

2 x 8 4 x 4 2 x 2 x 4 2 x 2 x 2 x 2

2 x 2 x 2 x 2 2 x 2 x 4 2 x 8 4 x 4

(x^2-4) (x^2+6x+8) __________ x _________ which is (x^2+2x-8) (x^2+4x+4) (x+2)(x-2) (x^2+4x+2x+8) ___________ x _____________ which is (x^2+4x-2x-8) (x^2+2x+2x+4) (x+2)(x-2) x(x+4)+2(x+4) ___________ x ____________ which is x(x+4)-2(x+4) x(x+2)+2(x+2) (x+2)(x-2) (x+2)(x+4) ________ x _________ which is 1 as all the terms in the num & den cancel (x-2)(x+4) (x+2)(x+2)

x + 2 = 4 x = 4 - 2 therefore: x = 2

x/4 - 4 = -2 Therefore, x/4 = -2 + 4 = 2 Therefore, x = 2 x 4 x = 8

You find numbers that divide evenly into 64, such as for example, 1, 2, 4, 8, 16, 32, and 64. Then sharpen your pencil and start writing. 1 x 64 = 64 2 x 32 = 64 4 x 16 = 64 8 x 8 = 64 2 x 2 x 16 = 64 2 x 4 x 8 = 64 4 x 4 x 4 = 64 2 x 2 x 2 x 8 = 64 2 x 2 x 4 x 4 = 64 2 x 2 x 2 x 2 x 4 = 64 2 x 2 x 2 x 2 x 2 x 2 = 64

heres the prime factorization of 1024: 1024 512 x 2 256 x 2 x 2 64 x 4 x 2 x 2 8 x 8 x 4 x 2 x 2 4 x 2 x 4 x 2 x 4 x 2 x 2 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 2 to the 10th power = 210

2 x 2 x 2 x 2 x 3 x 3 2 x 2 x 2 x 2 x 9 2 x 2 x 3 x 3 x 4 2 x 2 x 36 2 x 4 x 18 2 x 2 x 2 x 3 x 6 2 x 2 x 4 x 9 2 x 8 x 9 2 x 2 x 3 x 12 4 x 4 x 9 4 x 6 x 6 3 x 3 x 16 3 x 4 x 12 2 x 6 x 12 3 x 3 x 4 x 4 2 x 3 x 24

Use the chain rule:d/dx √(4 - x) = d/dx (4 - x)1/2= 1/2 (4 - x)-1/2 x d/dx (4 - x)= 1/2 (4 - x)-1/2 x -1= -1/2 (4 - x)-1/2 or -1/2√(4 - x)

That's a total of... 17148496850051.5

x/(x + 4) = 4/(x + 4) + 2 (x - 4)/(x + 4) = 2 x - 4 = 2x + 8 -x = 12 x = -12

6

4 x 4 2 x 8 2 x 2 x 4 2 x 2 x 2 x 2

3 x 2 x 4 = 24 (3 x 2) x 4 = 6 x 4 = 24 3 x (2 x 4) = 3 x 8 = 24 2 x (3 x 4) = 2 x 12 = 24

x^(2-x-6)/x^(2-4) x^(-4-x)/x^-2(x^-2)*(x^(-2-6))= x^(-2-x)

768 8 x 96 2 x 4 x 8 x 12 2 x 2 x 2 x 2 x 4 x 4 x 3 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 3

10 = 2 x 524 = 2 x 2 x 2 x 332 = 2 x 2 x 2 x 2 x 2LCM = 2 x 2 x 2 x 2 x 2 x 3 x 5 = 480

2 x 2 = 4.

-4

If I understand the problem correctly: x/(x+4) = 4/(x+4) + 2 (x-4)/(x+4) = 2 x - 4 = 2x + 8 x = -12